2014
DOI: 10.1155/2014/815945
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Analysis of Fluid-Structure Interaction and Flow Erosion of Gas-Solid Flow in Elbow Pipe

Abstract: A numerical simulation has been conducted to investigate flow erosion and pipe deformation of elbow in gas-solid two-phase flow. The motion of the continuous fluid phase is captured based on calculating three-dimensional Reynolds-averaged-Navier-Stokes (RANS) equations, while the kinematics and trajectory of the discrete particles are evaluated by discrete phase model (DPM), and a fluid-structure interaction (FSI) computational model is adopted to calculate the pipe deformation. The effects of inlet velocity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The solid particle was the second phase, there was no phase transition. (2) The solid particles of the incoming flow were evenly distributed in liquid water.…”
Section: Numerical Calculation Methods Of Elbow Jetmentioning
confidence: 99%
“…The solid particle was the second phase, there was no phase transition. (2) The solid particles of the incoming flow were evenly distributed in liquid water.…”
Section: Numerical Calculation Methods Of Elbow Jetmentioning
confidence: 99%
“…u = u at the interface of fluid-structure (12) σ . n = Г .n (13) where, σ is the Cauchy stress tensor, n is the unit normal, and Г is the real stress.…”
Section: Figure 1 Mesh For the Pipe And Fluid Domainmentioning
confidence: 99%
“…The FSI method is used for the analysis to calculate deformation. They concluded that erosion rate and deformation are connected to structural changes and inlet conditions [13]. In a study, a pipe flow is studied by using FSI to observe local damages.…”
Section: Introductionmentioning
confidence: 99%
“…With the deepening degree of erosion, the solid particles will eventually lead to pipeline leakage damage, influencing the environment and people's life [3]. Actual damaged pipelines are shown in Figure 1 [4]. Statistically, gas transmission stations in a given area, over six years, have undergone pipe perforations five times and serious pipe wall thinning three times.…”
Section: Introductionmentioning
confidence: 99%
“…(a) (b) Figure 1. Actual damaged pipelines [4] (a) a failure of bend after repairing; (b) a failure of bend in a gas pipeline.…”
Section: Introductionmentioning
confidence: 99%